Debating Investment Led Demand and Demand Led Investment - Khosla, Rajiv (Arthshastra Indian Journal of Economics & Research, 2019)
All the macroeconomic indicators for the Indian economy that are responsible for giving impetus to growth are pointing south. Some indicators like tax growth (at 20 years low), investment growth (at 17 years low), power (electricity) demand (at 12 years low), GDP (at 11 years low), and private consumption (at 7 years low) etc. have seen their stumpy growth in as much as a decade or two. It is argued that the fiscal stimulus provided by the government is misdirected towards the supply side, and it can yield results only after a time lag. Contrarily, demand side allocations through MGNREGA, PM-KISAN, and MUDRA moratorium could have yielded results in a shot span of time. The present study attempted to demystify the riddle if investment led demand or demand led investment could have offered favorable outcomes in a shorter time span.